Current management of Temporomandibular Joint Ankylosis in children and adolescents: Case Report. - Broggi Ángulo, Óscar Alfredo (2013)
The word 'ankylosis' is derived from ancient Greek, meaning 'a rigid joint', in this case associated to an impediment for progressive mouth opening, as a consequence of a fibrous, bony, or mixed tissue junction between the mandibular condyle and the mandibular fossa. This condition may occur as a sequel of mandible and face trauma, infectious diseases, or as a manifestation of chronic diseases leading to joint damage. This limitation in mouth opening may lead to poor oral hygiene, dental cavities, dental and facial deformities, and obstructive sleep apnea. Surgical therapy is mandatory in such cases, and there are many procedures described in the literature. Our objective is to show our surgical experience in 5 selected patients who were operated in our institution on the basis of the current surgical protocols.